2009
DOI: 10.1097/gco.0b013e3283292468
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the ‘at-risk’ fetus: Doppler ultrasound

Abstract: In this review, we will discuss current ultrasound Doppler literature and the recommendations of the experts. We observe that the best algorithm for incorporation of the ductus venosus into intrauterine growth restriction management is yet to be determined. This remains a subject of intense research aimed at optimizing pregnancy outcomes and will be important to follow to provide up-to-date care of our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 35 publications
2
29
0
1
Order By: Relevance
“…[7][8][9] Hypertension in pregnancy affects women of all ages. In the current study, maximum number of patients were in the 26-30yrs age.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Hypertension in pregnancy affects women of all ages. In the current study, maximum number of patients were in the 26-30yrs age.…”
Section: Discussionmentioning
confidence: 99%
“…It provides information on fetal and placental cardiovascular function on the basis of the blood flow dynamics measured in uterine, umbilical and fetal arteries [80]. A Cochrane review by Alfirevic et al comprising of 16 studies and involving 10, 225 babies had shown that fetal and umbilical artery Doppler ultrasound in high risk pregnancies can decrease the perinatal mortality by 29 % (RR 0.71, 95 % CI 0.52-0.98), when obstetric services were in place to ensure safe and timely delivery of the baby when needed.…”
Section: Discussionmentioning
confidence: 99%
“…30,35,36 In a meta-analysis of 16 studies in developed countries, doppler velocimetry of umbilical and fetal arteries in high-risk pregnancies was associated with a 29% reduction in perinatal mortality, but the specifi c eff ect on stillbirths was not signifi cant (table 1). 17 Ultrasound examinations are now readily available in many developing countries and, although the misuse of technology for female feticide has caused much concern, 37 with appropriate use and training, ultrasound and doppler examinations could be useful adjunctive health technologies in some middle-income countries.…”
Section: Screening and Intervention For High-risk Pregnancies And Fetmentioning
confidence: 99%